THE INFLUENCE OF FINANCIAL TECHNOLOGY ON BUMN BANKING PROFITABILITY 2014-2019 PERIOD - Lilly Linne A. Kainde; Jinny Maria Yasabeo (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
ABSTRACT This study was conducted to examine differences in profitability before and after using fintech with quantitative methods aimed at measuring profitability for the 2014-2019 period, using a comparison of profitability ratios, namely Return On Assets, Return On Equity, Net Interest Margin and Operating Expenses on Operating Income. Data information is based on the link between the Financial Services Authority and the population of state-owned banking financial statements, then defined using purposive sampling. The sample of this research is the quarterly financial reports that have been issued by banks. Analysis of research data using the Wilcoxon signed rank test. The results showed that the ROA value after fintech was higher than before, the ROE value after fintech was higher than before, the NIM value was higher after than before and the BOPO value was lower after than before. In conclusion, fintech can provide positive potential for banking profitability.